1990
DOI: 10.1093/jn/120.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Lipid Composition of Rat Testicular Plasma Membranes by Dietary (n-3) Fatty Acids Changes the Responsiveness of Leydig Cells and Testosterone Synthesis

Abstract: Experiments were conducted to assess whether changing dietary fat composition altered phospholipid composition of rat testicular plasma membranes in a manner that altered receptor-mediated action of luteinizing hormone (LH)/human chorionic gonadotropin (hCG). Weanling rats were fed diets that provided high or low cholesterol intakes and that were enriched with linseed oil, fish oil or beef tallow for 4 wk. Feeding diets high in (n-3) fatty acids decreased plasma and testicular plasma membrane 20:4(n-6) content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 28 publications
1
30
1
Order By: Relevance
“…This suggests that the testes or the epididymides have a very active FA metabolism that preferentially accumulates long-chain PUFAs, metabolizes PUFAs into long-chain metabolites more efficiently than other tissues, or both. In animal models, fish oil supplementation increases testicular concentrations of DHA (35,37,38). Further, the expression pattern of enzymes involved in PUFA metabolism in the testes suggests a very active FA metabolism.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests that the testes or the epididymides have a very active FA metabolism that preferentially accumulates long-chain PUFAs, metabolizes PUFAs into long-chain metabolites more efficiently than other tissues, or both. In animal models, fish oil supplementation increases testicular concentrations of DHA (35,37,38). Further, the expression pattern of enzymes involved in PUFA metabolism in the testes suggests a very active FA metabolism.…”
Section: Discussionmentioning
confidence: 97%
“…During sperm maturation, DHA concentrations exponentially increase in the sperm membrane (12) as a result of both dietary intake and local metabolism (34,35). Testes and sperm have higher concentrations of long-chain PUFAs, particularly DHA, than other tissues or cells (34,36).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been shown that dietary fat improves reproductive performance although the molecular mechanism has not yet been elucidated. Among the different theories, there is one that hypothesizes that dietary fat may directly increase steroidogenesis [37] or directly alter the receptor composition of the testicular plasma membranes [38,39]. …”
Section: Effects Of Fat Supplementation On Testosterone Biosynthesismentioning
confidence: 99%
“…Dietary fat composition appears to influence male reproductive function by modifying the number of spermatozoa per ejaculate [60]. In addition, dietary fat composition influences male reproductive function by affecting the cholesterol-phospholipid structure of testicular plasma membranes [61]. Detergents, like fatty acids, are amphipathic and also alter the activity of aminopeptidases in vitro [62].…”
Section: Dietary Factorsmentioning
confidence: 99%